2019
DOI: 10.1088/1361-6501/aafa66
|View full text |Cite
|
Sign up to set email alerts
|

Surface wave elastography: device and method

Abstract: Knowledge of the shear elasticity of soft tissues is relevant in many areas of medicine since some diseases correlate with changes in elasticity. Therefore, over the past 30 years, various noninvasive methods have been developed to estimate tissue elasticity. These methods are generally known as elastography. Most of them are ultrasound-based methods requiring specially adapted ultrasound scanners in order to quantify the elasticity. Elastography has the potential to add value and knowledge to other research a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Therefore, the experiments we carried out in this work did not include a direct comparison between the NU‐SWE and another known elastography method. Nevertheless, in previous works, we have performed such comparisons in phantoms and beef samples regarding the ultrasound shear wave elastography (Benech et al, ,2019, 2021; Grinspan et al, 2016). These studies showed that both approaches provide comparable results, especially within the range of frequencies employed in this work.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, the experiments we carried out in this work did not include a direct comparison between the NU‐SWE and another known elastography method. Nevertheless, in previous works, we have performed such comparisons in phantoms and beef samples regarding the ultrasound shear wave elastography (Benech et al, ,2019, 2021; Grinspan et al, 2016). These studies showed that both approaches provide comparable results, especially within the range of frequencies employed in this work.…”
Section: Discussionmentioning
confidence: 99%
“…If we consider the muscle like a transversely isotropic solid (Gennisson et al, 2005; Nordez & Hug, 2010), the longitudinal shear elastic modulus ( c 55 ) is related to a shear wave propagating in the muscle fibers direction with perpendicular polarization VT = c55false/ρ (where ρ is the muscle mass density = 1000 kg/m 3 ; Benech et al, 2019). Due to the arrangement of the wave source and the linear array of vibration sensors (Figure 1a), the NU‐SWE retrieves VT.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations